Wavelet analysis in a structured clay soil using 2-D images - J. A. Piñuela; D. Andina; K. J. McInnes; A. M. Tarquis (Nonlinear Processes in Geophysics, 2007)
The spatial variability of preferential pathways for water and chemical transport in a field soil, as visualized through dye infiltration experiments, was studied by applying multifractal and wavelet transform analysis (WTA). After dye infiltration into a 4 m² plot located on a Vertisol soil near College Station, Texas, horizontal planes in the subsoil were exposed at 5 cm intervals, and dye stain patterns were photographed. Box-counting methods and WTA were applied to all of the 16 digitalized high-resolution dye images and to the dye-mass image obtained merging all sections. The well-known Devil's staircase multifractal was also used to illustrate wavelet-based analysis. Our results suggest that wavelet methods can complement box-counting analysis in the context of multiscaling structure analysis.